2019
DOI: 10.3847/1538-3881/ab487f
|View full text |Cite
|
Sign up to set email alerts
|

Kojima-1Lb Is a Mildly Cold Neptune around the Brightest Microlensing Host Star

Abstract: We report the analysis of additional multiband photometry and spectroscopy and new adaptive optics (AO) imaging of the nearby planetary microlensing event TCPJ05074264+2447555 (Kojima-1), which was discovered toward the Galactic anticenter in 2017 (Nucita et al.). We confirm the planetary nature of the light-curve anomaly around the peak while finding no additional planetary feature in this event. We also confirm the presence of apparent blending flux and the absence of significant parallax signal reported in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 65 publications
0
24
1
Order By: Relevance
“…Finding microlensing events requires frequent monitoring of a large Table 3 Microlensing Optical Depth and Average Timescales in EROS Fields (Rahal et al 2009) Region area along the Galactic plane. This is why the first Galactic plane events were detected mostly serendipitously (e.g., Fukui et al 2007Fukui et al , 2019Gaudi et al 2008;Nucita et al 2018;Zang et al 2019). Only the recent few years have brought about more detections of microlensing events in the Galactic plane, mostly thanks to efforts by the Gaia and ZTF groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finding microlensing events requires frequent monitoring of a large Table 3 Microlensing Optical Depth and Average Timescales in EROS Fields (Rahal et al 2009) Region area along the Galactic plane. This is why the first Galactic plane events were detected mostly serendipitously (e.g., Fukui et al 2007Fukui et al , 2019Gaudi et al 2008;Nucita et al 2018;Zang et al 2019). Only the recent few years have brought about more detections of microlensing events in the Galactic plane, mostly thanks to efforts by the Gaia and ZTF groups.…”
Section: Discussionmentioning
confidence: 99%
“…Fukui et al (2007) and Gaudi et al (2008) presented the discovery of a bright microlensing event in the constellation Cassiopeia (l=117°). Nucita et al (2018), Fukui et al (2019), and Zang et al (2019) reported the characterization of a planetary-mass companion in microlensing event TCP J05074264+2447555 that was located toward the Galactic anticenter (l=179°). This was the first event, in which the two images generated by microlensing were resolved thanks to the use of the Very Large Telescope Interferometer GRAVITY (Dong et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the blended light basically all comes from the lens. Fukui et al (2019) detected no contamination at the position of the microlens on their Keck AO images, and using priors of an upper limit of p E and q E measured by Dong et al (2019), they found that the majority of the blend is most likely from the lens star rather than an ambient star or a companion to the source or the lens star. Our analysis directly measures the lens mass and distance using measured p E and q E , thus it is a direct demonstration that the blend mostly comes from the lens.…”
Section: Klmentioning
confidence: 96%
“…To estimate the lens apparent brightness, we use the angular Einstein radius q =  1.891 0.014 E mas and p =  0.469 0.060 E of the "luminous lens" model, and follow the procedure in Section 4.1. For extinction, we adopt the extinction law of Cardelli et al (1989) and estimate the extinction of the lens using the function of Fukui et al (2019). The predicted lens apparent magnitude is shown in Table 3.…”
Section: Klmentioning
confidence: 99%
See 1 more Smart Citation